The Efforts of Maintaining the Outpatients' Loyalty of X Hospital - Marten Bhara Suryo Aji; Nuryakin . (Jurnal Admmirasi, 2021)
This study themed expectations of service quality, patients’ satisfaction, and patients’ loyalty. This theme is considered in accordance with the mission of the hospital and in the national context that is in line with JKN (National Health Insurance) spirit that targets Universal Health Coverage (UHC) in 2019. This study used quantitative research, the design was cross-sectional, without giving any treatment to the subjects. The research method used was a survey research method. Average patients in X Hospital stated that they were dissatisfied with the dimensions of Reliability, Assurance, Empathy, Accessibility, and Affordability. However, the dimensions of tangibles and responsiveness were suitable for what patients got in the service. There is a gap between the expectation of service quality affecting the satisfaction of outpatients in X Hospital. Expectation variable has a significant effect on satisfaction, and satisfaction variable does not have a significant effect on loyalty, so it can be concluded that satisfaction variable does not mediate the effect of expectation on loyalty.